Insurance demand and social comparison: An experimental analysis - Friedl, Andreas; Lima de Miranda, Katharina; Schmidt, Ulrich (Journal of Risk and Uncertainty, 2014)
This paper analyzes whether social comparison can explain the low take-up of disaster insurance usually reported in field studies. We argue that risks in the case of disasters are highly correlated between subjects whereas risks for which high insurance take-up can be observed (e.g. extended warranties or cell phone insurance) are typically idiosyncratic. We set up a simple model with social reference points and show that in the presence of inequality aversion social comparison makes insurance indeed less attractive if risks are correlated. In addition we conducted a simple experiment which confirms these theoretical results. The average willingness to pay for insurance is significantly higher for idiosyncratic than for correlated risks.
Keywords: Disaster insurance; Social reference points; Loss aversion; Inequality aversion